A relational perspective on the contract-control-trust nexus in an interfirm relationship. (March 2017) - Minnaar, Reinald A.; Vosselman, Ed; van Veen-Dirks, Paula M.G.; Zahir-ul-Hassan, Muhammad Kaleem
Abstract: This paper makes sense of the contract-control-trust nexus in interfirm relationships by exposing the performativity of a contract and its incorporated control structures in generating trust. In our study of an outsourcing relationship between Semorg (an international manufacturer of semi-conductors) and Fasorg (the provider of facility management services), we find that trust is interactively related to control in complex and often unpredictable ways rather than in linear ways that result from managerial decision-making. In the network of associations that constitutes the interfirm relationship, trust is not a stable solution that generates predictability, but a quasi-actor that is made to act by the contract and the incorporated control structures. As a quasi-actor, trust is fluent and performative. Once in existence, it mobilises human actors and shapes the relationship. Thus, from a relational perspective trust is a possible and to a large extent unpredictable network effect. This differs from the rational perspective in which trust is an expectation that (in multiple categories) straightforwardly emerges and develops from managerial decisions.